2022
DOI: 10.1155/2022/8123157
|View full text |Cite
|
Sign up to set email alerts
|

STING Induces Liver Ischemia-Reperfusion Injury by Promoting Calcium-Dependent Caspase 1-GSDMD Processing in Macrophages

Abstract: Objectives. Although a recent study reported that stimulator of interferon genes (STING) in macrophages has an important regulatory effect on liver ischemia-reperfusion injury (IRI), the underlying mechanism of STING-dependent innate immune activation in liver macrophages (Kupffer cells, KCs) remains unclear. Here, we investigated the effect of STING on liver macrophage pyroptosis and the associated regulatory mechanism of liver IRI. Methods. Clodronate liposomes were used to block liver macrophages. AAV-STING… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…In addition, in steatotic livers, I/R injury induces pyroptosis and aggravates hepatic injury through caspase-1 activation [ 109 ]. Furthermore, it has been suggested that the stimulator of interferon genes (STING) could exacerbate liver I/R injury by facilitating calcium-dependent caspase-1-GSDMD processing in macrophages [ 110 ]. Finally, Alaa et al found that the application of octreopeptide and melatonin can reduce inflammasome-induced pyroptosis by the iTLR4-NF-κB-NLRP3 pathway, thus attenuating hepatic I/R injury [ 111 ].…”
Section: Pyroptosis and I/r Injurymentioning
confidence: 99%
“…In addition, in steatotic livers, I/R injury induces pyroptosis and aggravates hepatic injury through caspase-1 activation [ 109 ]. Furthermore, it has been suggested that the stimulator of interferon genes (STING) could exacerbate liver I/R injury by facilitating calcium-dependent caspase-1-GSDMD processing in macrophages [ 110 ]. Finally, Alaa et al found that the application of octreopeptide and melatonin can reduce inflammasome-induced pyroptosis by the iTLR4-NF-κB-NLRP3 pathway, thus attenuating hepatic I/R injury [ 111 ].…”
Section: Pyroptosis and I/r Injurymentioning
confidence: 99%
“…As previously reported, STING has a relationship with upstream noncoding miRNAs, which base pair with downstream STING mRNA, culminating in reduced type I IFN production and restoration of liver function 30 . Moreover, calcium‐dependent caspase 1‐GSDMD‐mediated pyroptosis and the NLRP3‐mediated inflammasome were amplified following STING activation in hepatic IRI 31,32 . However, not exclusive to the liver, the STING pathway appears to be overactivated as an accelerator of IRI in multiple other organs, including the brain and gut 33,34 .…”
Section: Discussionmentioning
confidence: 66%
“…We previously showed that liver IR triggers macrophage STING activation [ 11 ], and STING inhibition attenuates different types of sterile inflammatory liver injuries, including liver IR [ 12 , 28 ]. A recent study reported that STING induces liver IR injury by promoting calcium-dependent caspase 1-Gasdermin D processing in macrophages [ 29 ]. Suppression of STING signaling alleviates liver inflammation and IR injury [ 30 ].…”
Section: Discussionmentioning
confidence: 99%